Nocturnal atmospheric synergistic oxidation reduces the formation of low-volatility organic compounds from biogenic emissions - Zang, Han; Luo, Zekun; Li, Chenxi; Li, Ziyue; Huang, Dandan; Zhao, Yue (Atmospheric chemistry and physics, 2024)
Volatile organic compounds (VOCs) are often subject to synergistic oxidation by different oxidants in the atmosphere. However, the exact synergistic-oxidation mechanism of atmospheric VOCs and its role in particle formation remain poorly understood. In particular, the reaction kinetics of the key reactive intermediates, organic peroxy radicals (RO2), during synergistic oxidation is rarely studied. Here, we conducted a combined experimental and kinetic modeling study of the nocturnal synergistic oxidation of α-pinene (the most abundant monoterpene) by O3 and NO3 radicals as well as its influences on the formation of highly oxygenated organic molecules (HOMs) and particles. We find that in the synergistic O3 + NO3 regime, where OH radicals are abundantly formed via decomposition of ozonolysis-derived Criegee intermediates, the production of CxHyOz HOMs is substantially suppressed compared to that in the O3-only regime, mainly because of the depletion of α-pinene RO2 derived from ozonolysis and OH oxidation by those arising from NO3 oxidation via cross reactions. Measurement–model comparisons further reveal that the cross-reaction rate constants of NO3-derived RO2 with O3-derived RO2 are on average 10–100 times larger than those of NO3-derived RO2 with OH-derived RO2. Despite a strong production of organic nitrates in the synergistic-oxidation regime, the substantial decrease in CxHyOz HOM formation leads to a significant reduction in ultralow- and extremely low-volatility organic compounds, which significantly inhibits the formation of new particles. This work provides valuable mechanistic and quantitative insights into the nocturnal synergistic-oxidation chemistry of biogenic emissions and will help to better understand the formation of low-volatility organic compounds and particles in the atmosphere.